2014
DOI: 10.1111/ans.12748
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic approach to a planned two‐stage hepatectomy for bilobar colorectal liver metastases

Abstract: Laparoscopic first-stage resection of tumours in the left liver can be safely combined with RPVL/RPVE to achieve adequate hypertrophy of the FLR, allowing subsequent right hepatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…If the projected remnant liver was less than 30% of total liver volume, if the risk of postoperative liver insufficiency was high, or if patients had resectable bilobar disease, portal vein embolisation or ligation, and/or 2-step staged hepatectomy was used. 18…”
Section: Preoperative Patient Managementmentioning
confidence: 99%
“…If the projected remnant liver was less than 30% of total liver volume, if the risk of postoperative liver insufficiency was high, or if patients had resectable bilobar disease, portal vein embolisation or ligation, and/or 2-step staged hepatectomy was used. 18…”
Section: Preoperative Patient Managementmentioning
confidence: 99%
“…Many studies report favorable outcomes after open two stage hepatectomies (TSH) for bi-lobar colorectal liver metastases (10,11) and more recently some authors have described a MIS approach to TSH (12,13). Fuks et al reported acceptable short-term outcomes such as a low conversion rate, minimal blood loss and low morbidity rates in their series of 26 patients who underwent a pure laparoscopic approach for TSH (12).…”
Section: Discussion Discussionmentioning
confidence: 99%
“…Kilburn et al describe a laparoscopic 1st stage and open 2nd stage approach to patients with bi-lobar colorectal liver metastases. The authors describe a benefit of fewer adhesions at the 2 nd stage operation with this approach.Furthermore, they added that laparoscopic portal vein ligation during the first stage was feasible and can save the patient a separate portal embolization procedure (13).…”
Section: Discussion Discussionmentioning
confidence: 99%
“…Laparoscopic liver resection has been increasingly performed due to its advantages over open liver resection, in terms of better surgical and postoperative outcomes in selected patients . Some case series reported the feasibility of two‐stage hepatectomy using laparoscopic approach . Each group used different procedures such as a laparoscopic first‐stage liver resection followed by an open second‐stage hepatectomy, laparoscopic first‐ and second‐stage hepatectomy, and etc.…”
Section: Two‐stage Hepatectomy For Patients With Bilateral Clmmentioning
confidence: 99%
“…85,86 Some case series reported the feasibility of two-stage hepatectomy using laparoscopic approach. [87][88][89] Each group used different procedures such as a laparoscopic first-stage liver resection High grade SOS was associated with more postoperative morbidity.…”
Section: Two-stage Hepatectomy Using Laparoscopic Approachmentioning
confidence: 99%